Der Grosse St.-Bernhard-Pass und seine Bedeutung für das westschweizerische Mittelland: Eine historisch-geographische Studie - Staub, Walther (ERDKUNDE, 1957)
In the western Swiss central plateau with Lake Neuenburg and wooded hills, with the watershed zone towards Lake Geneva, wheat fields, vineyards, villages and castles, can be found some of the most pleasant landscapes in Switzerland. It is a region of ancient settlement. On the shores of the three Jura lakes, Neuenburg, Biel and Murten Lake, remains of the Neolithic and Bronze Age pile dwellings are found. The rich finds of the Gallo-Roman La Tene at the lower end of Lake Neuenburg gave their name to the Late Iron Age. During the Roman period western Switzerland became the transit region for the approach to the Great St. Bernhard Pass. From Aosta in Italy the Roman legions crossed over into the Drauce valley and the lower Rhone valley and passed Martigny and St. Maurice to Lake Geneva. Aventicum became the great cultural and military centre between Alps and Jura: it was at the height of its importance from 100—260 A.D. After the breakdown of the Roman Empire north of the Alps around the year 450 A.D. western Switzerland became the scene of fighting between the Burgundians, settled there by the Romans, and the Alemanni advancing from the north. Thus western Switzerland came to be the region of the language and cultural boundary. In 536 A.D. both these Teutonic tribes were incorporated into the Kingdom of the Franks. After the division of the Frankish Empire at the treaty of Verdun in 843 a Kingdom of Burgundy, Lower Burgundy (Aries, Vienne) and High Burgundy, separated from the Carolin- gian Empire; Payerne in western Switzerland came to be the royal residence of High Burgundy (888-1032). Payerne also became the seat of a Cluniacensian Abbey with a renowned monastery church. The routeway to the Great St. Bernhard again acquired prominence: this time as a pilgrimage and trade route from the north to the south. When the St. Gotthard route was opened up in about 1200 A.D. it caused one of the greatest shifts in the European communication system; and western Switzerland lapsed from its former importance into a purely agricultural region. Partly as a result of territorial disintegration when the Waadt area came to be part of Savoy, but in particular due to great flood catastrophes which are known to have occurred from the 16th century onwards, large parts of western Switzerland, especially of the lake province, fell into great poverty. It was only in the 19th century resulting from the political re-organisation, i. e. foundation of the Kanton Waadt, and the correction of the Jura rivers (1868-1878) by which the levels of the three Jura lakes were lowered by 2,8 m. that the region recovered and attained its present prosperity.